Contemporary American painting : (Duell, Sloan and Pearce, 1945)
Introduction by Donald Bear. Includes paintings of 116 artists. Color and black-and-white plates along with photos of and information about the artists. No writing or highlighting. Lightly tanned. Green end papers with representations of artists' signatures. Black boards with silver lettering show edge and corner wear, bumped spine ends, light soiling, moisture marks at bottom edge (not affecting text). Secure binding. Smoke-free environment. Careful packing and prompt shipping.